Footshock-induced activation of the claustrum-entorhinal cortical pathway in freely moving mice - Huang, Wushuang; Qin, Jing; Zhang, Chunqing; Qin, Han; Xie, Peng (Physiological research, 2022)
Footshock is frequently used as an unconditioned stimulus in fear conditioning behavior studies. The medial entorhinal cortex (MEC) contributes to fear learning and receives neuronal inputs from the claustrum. However, whether footshocks can induce a neuronal response in claustrum-MEC (CLA-MEC) projection remains unknown. Here, we combined fiber-based Ca2+ recordings with a retrograde AAV labeling method to investigate neuronal responses of MEC-projecting claustral neurons to footshock stimulation in freely moving mice. We achieved successful Ca2+ recordings in both anesthetized and freely exploring mice. We found that footshock stimulation reliably induced neuronal responses to MEC-projecting claustral neurons. Therefore, the footshock-induced response detected in the CLA-MEC projection suggests its potential role in fear processin.
Keywords: Fear; cortex entorhinalis; Animals; strach; Neurons; zvířata; Mice; Calcium; Claustrum; neurony; klaustrum; vápník; Entorhinal Cortex; myši